2014
DOI: 10.24297/jap.v4i1.2054
|View full text |Cite
|
Sign up to set email alerts
|

AC Conductivity and Mechanism of Conduction Study of ?-Sr2P2O7 Using Impedance Spectroscopy

Abstract: The ceramic sample Sr2P2O7 was prepared by a solid-state reaction technique at high temperature. Electrical properties and modulus analysis were studied using complex impedance spectroscopy in the frequency range 200 Hz–5 MHz and temperature range 602-714 K. The difference of the value of activation energy for the bulk obtained from analysis of equivalent circuit (0.81 eV) and modulus relaxation (0.69 eV) confirms that the transport is not due from a simple hopping mechanism. The average of the power law expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…37,38 Stockmann explained the model for negative photo-conductivity occurrence. 39 From these results, it has been confined and concluded that the grown MOH inorganic single crystals are well used for photonic utility and electronic device appliances.…”
Section: Characterisationsmentioning
confidence: 97%
“…37,38 Stockmann explained the model for negative photo-conductivity occurrence. 39 From these results, it has been confined and concluded that the grown MOH inorganic single crystals are well used for photonic utility and electronic device appliances.…”
Section: Characterisationsmentioning
confidence: 97%